A study of bronchial asthma in school going children in Southern part of Rajasthan - Jain, Shubham; Luhadia, Atul; Luhadia, Shanti K.; Chhabra, Gaurav; Sharma, Rishi Kumar; Gupta, Amit S.; Bansal, Monica; Gupta, Sujit; Hanfe, Mohammed Hamza; Yadav, Vishal; Patel, Viren; Zota, Adit; et al. (International Journal of Research in Medical Sciences, 2021)
Background: Asthma is a chronic and common inflammatory disease involving mainly large airways of lungs. Childhood asthma is common chronic illness among school going children and is usually underdiagnosed and undertreated. The aim of the present study was to find out of the prevalence of Bronchial asthma in school going children of age group 6-12 years in southern part of Rajasthan (India), and its relation with gender, socio-economic status and heredity. Methods: A questionnaire-based study has been carried out in 1500 children of 6 to 12 years age group in four schools of Udaipur city (Rajasthan, India) with a response rate of 60.23% (904/1500). Results: The overall prevalence of asthma observed is 4.75% (43/904). The prevalence is higher among boys (5.55%) as compared to girls (3.75%). Further the prevalence is higher in upper (7.18%) and upper middle class (7.14%) children as compared to lower middle (4.84%) and upper lower class (2.01%) socioeconomic status. The children with positive family history of asthma also have higher prevalence (26.31%) of asthma. Conclusions: The prevalence of childhood asthma in Udaipur city is relatively lower and supports the already reported relation with gender, socioeconomic status and heredity.